Antibiotics-induced pulmonary embolism: A disproportionality analysis in Food and Drug Administration database of Adverse Event Reporting System using data mining algorithms - Pramod Kumar Adusumilli; Foujia Begum; Ankita Ashok Sangnure; Jeesa George (Perspectives in Clinical Research)
Background: Antibiotics are among the most commonly prescribed drugs. Unnecessary use of antibiotics is particularly concerning because antibiotics may be associated with a number of adverse drug events. Aim: The study was designed to detect the association between pulmonary embolism and antibiotics by disproportionality analysis in the Food and Drug Administration database of Adverse Event Reporting System (FAERS) using data mining algorithms (DMAs). Materials and Methods: A retrospective case/noncase disproportionality analysis was performed in the FAERS database. This study was based on adverse events (AEs) reported to FAERS from 2004 Q1 to 2022 Q3. Reporting odds ratio (ROR), proportional reporting ratio (PRR), and information component (IC) were applied to measure the disproportionality in reporting. A positive signal of increased AE risk was defined as ROR >1, Chi-square >4, PRR R2 with the number of cases >3, and IC >0. Results: Total AEs in the FAERS database from 2004 Q1 to 2022 Q3 were found to be 26,555,430. Among which 80,809 reports of pulmonary embolism were considered. The same were selected for further analysis which showed that 11 antibiotics were reported for pulmonary embolism. The number of reports for minocycline, chloramphenicol, and moxifloxacin was found to be 113, 14, and 179. A significant potential signal was noted for minocycline (ROR – 2.87, Chi-square – 135.95, IC – 1.22), chloramphenicol (ROR – 3.35, Chi-square – 22.80, IC – 0.77), and moxifloxacin (ROR – 2.08, Chi-square – 99.37, IC – 0.83). Conclusion: This study found a statistically significant increased risk of reporting pulmonary embolism with minocycline, chloramphenicol, and moxifloxacin, although a causal relation cannot be definitively established.